Personalisation in Dutch and German Politics: The Case of Talk Show - van Zoonen, Liesbet; Holtz-Bacha, Christina (Javnost-The Public, 2000)
Personal qualities of politicians play an ever more important role in present-day politics. This trend is usually defined as personalisation,. which we take in this study to consist of a complex interplay between personal characteristics of politicians and their mediation through various institutional practices, such as campaign strategies and media coverage, from which voters will build their perceptions of politicians. In this study the personal performance of Dutch and German politicians in talk shows was analysed, distinguishing four kinds of discourse that politicians could use: political discourse, personalised political discourse, personal discourse, and objectified discourse. It appeared that the genre conventions of talk shows favour personal discourse and personalised political discourse; nevertheless, politicians still are able to use political discourse. This depends, however, on the communicative capacities of politicians who must be able to switch from the personal discourse favoured in talk shows, through personalised political discourse to the political discourse more common to the political domain. The main difference found in the study was not between The Netherlands and Germany, but between the different kinds of talk shows.